Prevention of postpartal endometritis: Antibiotic of choice - Jovanović Nebojša (Srpski Arhiv za Celokupno Lekarstvo, 2009)
Introduction In spite of the advances of modern medicine, puerperal infection is still one of the leading causes of morbidity and mortality of women in postpartal period. Objective The aim of this study was to analyze the presence of microorganisms in the cervicovaginal region of women in labor, as well as the frequency of puerperal endometritis in order to determine optimal treatment for isolated microorganisms and to prevent postpartal endometritis. Methods In this study, all women who gave birth to a healthy child per vias naturalis during the past two years in a tertiary health institution, Institute of Gynaecology and Obstetrics, Clinical Centre of Serbia, were analyzed. The investigation involved 6,391 women in labor. Cervicovaginal smear was taken from all patients before labor, on admission for delivery, and sent to microbiological analysis. Standard procedures of bacterial cultivation were used. For statistical analysis of the results, we used the statistical programme SPSS 15. Results A single microorganism was isolated from each smear of 612 women and in 52 patients two microorganisms were registered in the same smear. We identified 10 sorts of microorganisms, out of which Escherichia coli (in 43.8% of cases), and Enterococcus spp. (in 27.9% of cases) were the most frequent ones. Due to the appropriate approach, there were no cases of puerperal endometritis registered. Reactivity tests showed that Escherichia coli was sensitive to trimethoprim-sulphamethoxazole, Enterococcus spp. to macrolides and cephalosporines, while both types of microorganisms were sensitive to synthetic penicillins and fluoroquinolines. Conclusion The study results show that 10.9% of pregnant women have positive findings of the cervicovaginal smear and that infection prevention should be directed towards Escherichia coli and Enterococcus spp. by administration of the listed antibiotics.